Elevated Level of PKMζ Underlies the Excessive Anxiety in an Autism Model - Gao, Xiaoli; Zheng, Rui; Ma, Xiaoyan; Gong, Zhiting; Xia, Dan; Zhou, Qiang (Frontiers in Molecular Neuroscience, 2019)
Anxiety affects the life quality of a significant percentage of autism patients. To understand the possible biological basis of this high anxiety level, we used a valproic acid (VPA) model of autism. Anxiety level is significantly higher in VPA-injected mice, at both P35 and P70. In addition, protein kinase M ζ (PKMζ) level in the basolateral amygdala (BLA) is significantly higher in VPA mice at both ages. Consistent with this finding, infusion of a PKMζ-blocking peptide z-pseudosubstrate inhibitory peptide (ZIP) into BLA significantly reduced anxiety levels in VPA mice. Furthermore, viral overexpression of PKMζ in the BLA led to elevated anxiety level in Wild Type (WT) mice, with concomitant higher intrinsic excitability of BLA excitatory neurons. Altogether, our results indicate a key contribution of BLA PKMζ level to anxiety, especially in autism; and this finding may provide further understanding of the pathogenesis as well as treatment of anxiety symptoms in autism patients.